2010
DOI: 10.1186/1471-2296-11-28
|View full text |Cite
|
Sign up to set email alerts
|

U.S. healthcare providers' knowledge, attitudes, beliefs, and perceptions concerning Chronic Fatigue Syndrome

Abstract: BackgroundChronic fatigue syndrome (CFS) is a debilitating illness with particular difficulties for healthcare providers because there are no diagnostic signs or laboratory tests and because management aims to merely improve symptoms. Further complicating management, healthcare providers' awareness concerning CFS has not been rigorously assessed. The present study aimed to ascertain United States (U.S.) healthcare providers' awareness of CFS and to assess their knowledge, attitudes, and beliefs (KAB) related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…This reliance on medical journals and Internet sites is in agreement with previous studies that examined where physicians looked for their information (Brimmer, Fridinger, Lin, & Reeves, 2010). There were several potential limitations to our study.…”
Section: Discussionsupporting
confidence: 84%
“…This reliance on medical journals and Internet sites is in agreement with previous studies that examined where physicians looked for their information (Brimmer, Fridinger, Lin, & Reeves, 2010). There were several potential limitations to our study.…”
Section: Discussionsupporting
confidence: 84%
“…To ensure that adequate representation of targeted provider specialties was obtained, the 2009 DocStyles survey used quota sampling, a form of nonprobability sampling in which the proportions of selected participant characteristics within the sample are deliberately set. [10][11][12] The DocStyles survey has been used to explore a variety of topics, including chronic fatigue syndrome 13 and immunodeficiency diseases. 14 CDC licensed the results of the 2009 DocStyles survey from Porter Novelli (Washington, D.C.).…”
Section: Methodsmentioning
confidence: 99%
“…This raises the potential for overdiagnosis or underdiagnosis. For example, in one study 40% of American physicians reported making a diagnosis of CFS, 4 and in another study less than 20% of persons with the illness had been given the diagnosis. 5 …”
Section: Introductionmentioning
confidence: 99%